Quantum of solace [videorecording (Blu-Ray)] - Forster, Marc, 1969-; Craig, Daniel, 1968-; Dench, Judi, 1934-; Amalric, Mathieu, 1965-; Kurylenko, Olga, 1979-; Arnold, David, 1962-; Schaefer, Roberto (Metro-Goldwyn-Mayer, 2015)
Fighting the urge to seek revenge for the death of a friend, James Bond seeks out the mysterious organization known as "Quantum" to destroy them before they can take control of an important natural resource.